PENGEMBANGAN MEDIA PEMBELAJARAN MIMIMAT(MINIATUR MINIMARKET MATEMATIKA) UNTUK MENINGKATKAN PEMAHAMAN KONSEP MATEMATIKA MATERI PENJUMLAHAN BERSUSUN KELAS III - Faiza Mujtahida Noor; Rida Fironika Kusumadewi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low understanding of students towards the concept of compound addition and the lack of use of interesting and interactive learning media in the mathematics learning process in elementary schools. Therefore, MIMIMAT learning media was developed to help students understand the concept of compound addition more easily and enjoyably. This study aims to analyze the validity, practicality, and effectiveness of MIMIMAT media on the understanding of the concept of compound addition. This study aims to analyze the validity, practicality, and effectiveness of MIMIMAT media and its influence on the understanding of the concept of compound addition of grade III students. The study used the Research and Development (R&D) method with the ADDIE model. Data were collected through expert validation, questionnaires, tests, interviews, and observations, then analyzed descriptively and inferentially. The results of the study indicate that MIMIMAT media meets the valid criteria based on the assessment results of material experts and media experts. The media was also declared practical based on teacher and student responses that showed a good category. Statistical tests showed a significant increase in conceptual understanding (Sig. = 0.013) with an N-Gain value of 0.60 (moderate category). This finding confirms that the use of MIMIMAT media is in line with constructivism theory which states that students more easily understand concepts when directly involved in the learning process through concrete media and meaningful learning experiences. In addition, MIMIMAT media supports an active learning approach because it is able to help students build an understanding of the concept of compound addition gradually and systematically. Keywords: MIMIMAT, learning media, compound addition, conceptual understanding,